Agent-Based Aplications for the Smart Grid--A Playground for Agreement Tecnologies - Ossowski, Sascha (My University, 2014)
Agreement Technologies (AT) refer to computer systems in which autonomous software agents negotiate with one another, typically on behalf of humans, in order to come to mutually acceptable agreements. The talk first briefly delineates the emerging field of AT, and then points to several case studies showing how findings from the field of AT can be used for building advanced applications for the Smart Grid.
Keywords: Inteligencia artificial